Electrolytic Behavior Silver Microphases and Nanophases on the Graphite Electrode Surface; Key Engineering Materials; Vol. 712 : Advanced Materials for Technical and Medical Purpose (AMTMP 2016) - Perevezentseva D. O. Dariya Olegovna (Electrophysical and Electrochemical Methods and Technologies of Materials Treatment, 2016)
Title screen